Religia, sztuka i przemoc. Wokół ikonografii konfliktu ulsterskiego - Zydorowicz, Jacek (Polskie Towarzystwo Religioznawcze, 2011)
Jacek Zydorowicz – RELIGION, ART AND VIOLENCE. AN ICONOGRAPHY OF ULSTER CONFLICT There is a kind of consensus among the observers of the contemporary terrorism about the propaganda impact of strong, suggestive images delivered by the media. The more perfectly docu-mented a terrorist act is, the more global media resonance it causes. In the 80s of the 20th century Margaret Thatcher suggested cutting off „the oxygen of publicity” for the IRA spokespeople. This gesture brought about an explosion of the images on the local level. Protestant and Catholic artists accelerated their fight on Belfast and Derry walls. Its worth pondering on the religious background of murals by looking at their iconography.